Stereospecific route to 5,11-methanomorphanthridine alkaloids via intramolecular 1,3-dipolar cycloaddition of nonstabilized azomethine ylide: Formal total synthesis of (+/-)-pancracine - Pandey, Ganesh; Banerjee, Prabal; Kumar, Ravindra; Puranik, Vedavati G. (Organic Letters, 2005)
[GRAPHICS] The core structure of the complex pentacyclic 5,11-methanomorphanthridine alkaloids is constructed stereospecifically in one step employing an intramolecular [3 + 2]-cycloaddition of nonstabilized azomethine ylide as the key step. The strategy is demonstrated by accomplishing the formal total synthesis of (+/-)-pancracine.

Beta-lactam-azasugar hybrid as a competitive potent galactosidase inhibitor - Pandey, Ganesh; Dumbre, Shrinivas G.; Khan, Mohammad Islam; Shabab, M.; Puranik, Vedavati G. (Tetrahedron Letters, 2006)
A beta-lactam-azasugar hybrid (polyhydroxylated carbacephem) has been designed and synthesized as a potent glycosidase inhibitor. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: beta-Galactosidase; beta-lactam-azasugar; glycosidase inhibitor; hybrid molecules

Construction of enantiopure pyrrolidine ring system via asymmetric [3+2]-cycloaddition of azomethine ylides - Pandey, Ganesh; Banerjee, Prabal; Gadre, Smita R. (Chemical Reviews, 2006)

Convergent approach toward the synthesis of the stereoisomers of C-6 homologues of 1-deoxynojirimycin and their analogues: evaluation as specific glycosidase inhibitors - Pandey, Ganesh; Dumbre, Shrinivas G.; Khan, Mohammad Islam; Shabab, M. (Journal of Organic Chemistry, 2006)
A new and stereoselective strategy is developed to synthesize an appropriate template 9 to obtain C-6 homologues of 1-deoxyazasugars such as 1-deoxy-D-galactohomonojirimycin ( 5), 1-deoxy-4-hydroxymethyl-D-glucohomonojirimycin (6), and their enantiomers. The template 9 is also used to obtain neutral nonbasic pseudo-glyconolactam (8), C-4 amino, and methyl analogues of 1-deoxy- homonojirimycin as new analogues of 1- deoxyhomoazasugars. Compound 5 is found to be a potent and specific inhibitor to alpha-galactosidase (K-i = 1.7 mu M). Similarly compounds 6 (K-i = 28 mu M), ent-5 (K-i = 129 mu M), and ent-6 K-i = 12 mu M) exhibited specific inhibition of beta-glucosidase.

Synthesis and evaluation of 1-deoxy-8-epi-castanospermine, 1-deoxy-8-hydroxymethyl castanospermine, and (6S,7S,8R,8aR)-8-amino-octahydroindolizine-6,7-diol - Pandey, Ganesh; Dumbre, Shrinivas G.; Pal, Sujit; Khan, Mohammad Islam; Shabab, A. (Tetrahedron, 2007)
A short, versatile, and enantioselective synthesis of 1-deoxy-8-epi-castanospermine (5), 1-deoxy-8-hydroxymethyl castanospermine (6), and (6S,7S,8R,8aR)-8-amino-octahydroindolizine-6,7-diol (7) is achieved from a common template 12. The key step utilized is PET provoked amine radical cyclization of 11 to 12 in excellent diastereoselectivity. The exocyclic double bond at C-8 of the template is functionalized to obtain 5-7 as exclusive diastereomers. 1-Deoxy-8-epi-castanospermine exhibited inhibition of alpha- and beta-galactosidase and beta-glucosidase. Compounds 6 and 7 were found to be weak inhibitors of beta-glucosidase. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: 1-deoxy-8-epi-castanospermine; castanospermine; Glycosidase inhibitors

Suzuki cross-coupling and intramolecular aza-michael addition reaction sequence towards the synthesis of 1,10b-epi-7-deoxypancratistatins and their cytotoxicity studies - Pandey, Ganesh; Balakrishnan, Madhesan; Swaroop, Pandrangi Siva (European Journal of Organic Chemistry, 2008)
The development of an efficient approach to the construction of a phenanthridone is described. The convergent strategy commences with the preparation of Suzuki cross-coupling reaction precursors, arylboronic acid 12 and a-iodo enone 14, from piperonylamine (9) and (-)-D-quinic acid (10), respectively. The coupling of 12 and 19 followed by a key intramolecular aza-Michael addition produced phenanthridone 21 featuring a cis-fused B-C ring junction. The syntheses of compounds 25 and 26, both of which are C-1 and C-10b epimers of the naturally occurring potent antitumor agent 7-deoxypancratistatin (2), from 21 are elaborated in detail in this paper. The cytotoxicities of 25 and 26 were evaluated against three different cancer cell lines. Compound 26 served as a moderate growth inhibitor of THP-1 monocytic cells (GI(50) = 14.5 mu g/mL). ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)
Keywords: antitumor agents; Chiral pool; Cross-coupling; Intramolecular aza-Michael addition; Pancratistatin

Suzuki cross-coupling/reductive debenzyloxycarbonylation sequence for the syntheses of [c]annulated isoquinolines: application for the syntheses of pancratistatin-like isoquinolines - Pandey, Ganesh; Balakrishnan, Madhesan (Journal of Organic Chemistry, 2008)
A two-step strategy involving Suzuki cross-coupling of boronic acids with a diverse array of alpha-iodoenones followed by hydrogenation is developed for the construction of [c]annulated isoquinolines. This mild and efficient procedure is also applied to the synthesis of highly oxygenated isoquinolines.

Synthesis of polyhydroxy piperidines and their analogues: a novel approach towards selective inhibitors of alpha-glucosidase - Pandey, Ganesh; Bharadwaj, Kishor Chandra; Khan, Mohammad Islam; Shashidhara, K. S.; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2008)
Various polyhydroxy piperidine azasugars have been synthesized from precursors 18a and 18b, obtained in both enantiomeric forms from D-ribose. Out of these polyhydroxy piperidine azasugars, 22, 39 and 20 were found to be potent as well as selective inhibitors of a-glucosidase with K(i) values ranging as low as 1.07 mu M, 16.4 mu M, and 88.2 mu M, respectively. Replacement of the hydroxy methylene moiety of 19 (K(i) 33% at 1 mM) by an amino methylene moiety (32, K(i) 36.8 mu M) showed a remarkable increase in the activity (almost 30 times). Furthermore, increasing the lipophilicity of 33 by N-alkylation with a dodecyl group (36) showed a three-fold enhancement in the activity (K(i) 217 mu M to K(i) 72.3 mu M).

Use of enantiomerically pure 7-azabicyclo[2.2.1]heptan-2-ol as a chiral template for the synthesis of aminocyclitols - Pandey, Ganesh; Tiwari, Keshri Nath; Puranik, Vedavati G. (Organic Letters, 2008)
Using enantiopure 7-azabicyclo[2.2.1]heptane-2-ol, the synthesis of cis- as well as trans-2-aminocyclohexanols, dihydroconduramine E-1, and ent-conduramine F-1 has been described.

Enantioselective total synthesis of (2S,3R,4R)-D-xylo-phytosphingosine from substituted azetidin-2-one - Pandey, Ganesh; Tiwari, Dharmendra Kumar (Tetrahedron Letters, 2009)
Enantiomerically pure (2S,3R,4R)-D-xylo phytosphingosine is synthesized in 36% overall yield in seven steps from known beta-lactam (8) derived from D-mannitol triacetonide. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: beta-lactam; Enantioselective synthesis; Sphingosine; Wittig reaction

Stereoselective one-step construction of vicinal quaternary and tertiary stereocenters of the 5,10b-ethanophenanthridine skeleton: total synthesis of (+/-)-maritidine - Pandey, Ganesh; Gupta, Nishant R.; Pimpalpalle, Tukaram M. (Organic Letters, 2009)
The challenging vicinal quaternary and tertiary stereocenters of the 5,10b-ethanophenanthridine skeleton are created in a single step utilizing intramolecular [3 + 2]-cycloaddition of nonstabilized azomethine ylide as the key step. The application of the chemistry is demonstrated by synthesizing (+/-)-maritidine.

Synthesis of polyfunctional quinolizidine alkaloids: development towards selective glycosidase inhibitors - Pandey, Ganesh; Grahacharya, Debasish; Shashidhara, K. S.; Khan, Mohammad Islam; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2009)
A highly divergent route to a variety of quinolizidine alkaloids is described. The enantiomeric precursors 22a and 22b utilized for the synthesis of these alkaloids were constructed stereospecifically from the PET cyclization of the corresponding acetylene tethered alpha-trimethylsilyl amine moieties 21a and 21b, respectively, both of which were synthesised from D-ribose. The polyhydroxy quinolizidine alkaloid 7 was found to be a selective inhibitor of alpha-galactosidase with Ki 83.9 mu M. The amine analogs 18, 12 and 10 are found to be selective and potent inhibitors of alpha-glucosidase with Ki 28, 120 and 140 mu M, respectively.

Synthesis of optically pure 2,3,4-trisubstituted tetrahydrofurans via a two-step sequential Michael-Evans aldol cyclization strategy: total synthesis of (+)-magnolone - Pandey, Ganesh; Luckorse, Srikanth; Budakoti, Asha; Puranik, Vedavati G. (Tetrahedron Letters, 2010)
Synthesis of optically pure 2,3,4-trisubstituted tetrahydrofurans is described employing a two-step Michael-Evans aldol cyclization strategy. The approach is successfully applied for the total synthesis of furano lignan natural product (+)-magnolone. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: HWE reaction; Lignans; Magnolone; Michael-Evans aldol reaction; Tetrahydrofuran

Construction of the 5,10b-phenanthridine skeleton using [3+2]-cycloaddition of a non-stabilized azomethine ylide: total synthesis of (+/-)-maritidine and (+/-)-crinine alkaloids - Pandey, Ganesh; Gupta, Nishant R.; Gadre, Smita R. (European Journal of Organic Chemistry, 2011)
Vicinal quaternary and tertiary stereocenters of the 5,10b-phenanthridine skeleton 1 are constructed simultaneously in one step by the [3+2]-cycloaddition of non-stabilized azomethine ylide 9, generated by sequential double desilylation of 10 utilizing silver(I) fluoride as a one-electron oxidant. The regioas well as stereochemical origin of this cycloaddition reaction is explained through a favorable transition state 9''. The strategy is successfully applied for the total synthesis of the biologically active alkaloids (+/-)-maritidine (1a), (+/-)-crinine (1b), and their analogues (1d, 1e, and 1f).
Keywords: alkaloids; Azomethine ylides; Cycloaddition; Natural products; Ylides

Enantioselective total syntheses of (-)-isonitramine, (-)-sibirine, and (+)-nitramine by ring-closing metathesis - Pandey, Ganesh; Kumara, Prasanna C.; Burugu, Shiva Kumar; Puranik, Vedavati G. (European Journal of Organic Chemistry, 2011)
Concise enantioselective total syntheses of naturally occurring 2-azaspiro[5,5]undecan-7-ol (Nitraria) alkaloids viz. ()-isonitramine, ()-sibirine, and (+)-nitramine are accomplished in 42, 38, and 25?% overall yield, respectively, in six steps starting from enantiomerically pure (S)-methyl 3-allyl-2-oxo-1,2,3,6-tetrahydropyridine-3-carboxylate (>99?%?ee). The key feature of the syntheses involves diastereoselective HosomiSakurai allylation followed by ring-closing metathesis.
Keywords: Alk-aloids; Allylation; Amino alcohols; Metathesis; Total synthesis

Iminium ion cascade reaction in the total synthesis of (+)-vincadifformine - Pandey, Ganesh; Kumara, Prasanna C. (Organic Letters, 2011)
An iminium ion triggered cascade reaction is described in the total synthesis of (+)-vincadifformine by the coupling of 3,3-substituted tetrahydropyridine and indole derivative. The strategy allows simultaneous construction of two new rings, three new sigma bonds, and two new stereogenic centers in one pot with complete stereochemical control.

One-step stereospecific strategy for the construction of the core structure of the 5,11-methanomorphanthridine alkaloids in racemic as well as in optically pure form: synthesis of (+/-)-pancracine and (+/-)-brunsvigine - Pandey, Ganesh; Kumar, Ravindra; Banerjee, Prabal; Puranik, Vedavati G. (European Journal of Organic Chemistry, 2011)
The unique core structure of the complex pentacyclic 5,11-methanomorphanthridine has been constructed stereospecifically in one step by an intramolecular [3+2] cycloaddition of a non-stabilized azomethine ylide (AMY), generated by the sequential double desilylation of 14 using (AgF)-F-I as a one-electron oxidant. The formation of the single diastereomer in the key step is explained by the preferred transition state produced by endo attack of the AMY on the ``Re'' face of the dipolarophile. An asymmetric version of the cycloaddition using a chiral dipolarophile was applied to construct the core structure 68 with 63 % ee. This strategy was successfully applied to the formal synthesis of (+/-)-pancracine and the total synthesis of (+/-)-brunsvigine. An unprecedented and interesting skeletal rearrangement product 49 was observed during the attempted assembly of the E ring from 46 through Horner-Wadsworth-Emmons reactions. Mechanisms involving azetidinium salt formation or the Grob-type fragmentation are advanced to explain the observed rearrangement.
Keywords: alkaloids; Azomethine ylides; Cycloaddition; Ring-closing metathesis; synthesis design

Temperature-guided diastereoselectivity switch during the desymmetrization of meso-7-azabicyclo[2.2.1]heptadiene: new strategy towards the synthesis of aminocyclitols - Pandey, Ganesh; Rajender, Salla (Chemistry-A European Journal, 2011)
Keywords: aminocyclitols; azabicycloheptane; desymmetrization; diastereoselectivity; synthetic methods

Dimethyl [(2R,3R,5S)-5-phenylmorpholine-2,3-diyl]diacetate as a designer substrate in the syntheses of important heterocyclic scaffolds - Pandey, Ganesh; Gaikwad, Amrut L.; Gadre, Smita R. (Asian Journal of Organic Chemistry, 2012)
Designed scaffold dimethyl [(2R,3R,5S)-5-phenylmorpholine-2,3-diyl]diacetate was synthesized in optically pure form by photoinduced one-electron reductive beta-activation of an alpha,beta-unsaturated carbonyl moiety for stereoselective C-C bond formation. Use of the morpholine derivative as a ``chemical multitalent'' is demonstrated by its easy transformation to valuable heterocyclic building blocks such as methyl [(2R,3S)-3-hydroxy-5-oxopyrrolidin-2-yl]acetate, methyl [(2R,3S)-3-amino-5-oxotetrahydrofuran-2-yl]acetate, (3R,4S)-4-aminohexane-1,3,6-triol, and 2-[(2R,3S)-3-aminotetrahydrofuran-2-yl]ethanol.
Keywords: Amino alcohols; butyrolactams; butyrolactones; morpholines; photoinduced electron transfer reactions

Organocatalytic dynamic kinetic resolution via conjugate addition: synthesis of chiral trans-2,5-dialkylcyclohexanones - Pandey, Ganesh; Adate, Priyanka A.; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2012)
A novel strategy of initiating an organocatalysed dynamic kinetic resolution (dr up to 99 : 1 and er up to 94 : 6) for the synthesis of chiral trans-2,5-dialkylcyclohexanones by an asymmetric conjugate addition of dimethyl malonate on to 6-substituted cyclohexenones is reported.

Stereoselective construction of 5,11-methanomorphanthridine and 5,10b-phenanthridine structural frameworks: total syntheses of (+/-)-pancracine, (+/-)-brunsvigine, (+/-)-maritidine, and (+/-)-crinine - Pandey, Ganesh; Gadre, Smita R. (Pure and Applied Chemistry, 2012)
The core structure of the complex pentacyclic 5,11-methanomorphanthridine skeleton and the vicinal quaternary and tertiary stereocenters of the 5,10b-phenanthridine skeleton are constructed stereospecifically in one step employing intramolecular 1,3-dipolar cyclo addition of a nonstabilized azomethine ylide (AMY) generated by the sequential double desilylation of appropriate bis-trimethylsilylmethyl amines using Ag(I)F as a single-electron oxidant. The strategy is successfully applied for the total synthesis of biologically active alkaloids such as (+/-)-pancracine, (+/-)-brunsvigine, (+/-)-maritidine, and (+/-)-crinine.
Keywords: alkaloid synthesis; cycloadditions; organic synthesis; stereocontrolled synthesis

Visible light photoredox catalysis: generation and addition of N-aryltetrahydroisoquinoline-derived alpha-amino radicals to michael acceptors - Kohls, Paul; Jadhav, Deepak; Pandey, Ganesh; Reiser, Oliver (Organic Letters, 2012)
The photoredox-catalyzed coupling of N-aryltetrahydroisoquinoline and Michael acceptors was achieved using Ru(bpy)(3)Cl-2 or [Ir(ppy)(2)-(dtb-bpy)]PF6 in combination with irradiation at 455 nm generated by a blue LED, demonstrating the trapping of visible light generated alpha-amino radicals. While intermolecular reactions lead to products formed by a conjugate addition, in intramolecular variants further dehydrogenation occurs, leading directly to 5,6-dihydroindolo[2,1-a]tetrahydroisoquinolines, which are relevant as potential immunosuppressive agents.

Alpha-trimethylsilylmethylamine radical cation in the synthesis of cyclic amines and beyond - Pandey, Ganesh; Dey, Debasis; Gadre, Smita R. (Chimia, 2013)
The evolution of chemistry associated with the photoinduced electron transfer (PET)-generated alpha-trimethylsilylmethylamine radical cation cyclization to a tethered olefin to synthesize byclic amine structural frame works is presented in chronological order. The importance of this interesting chemistry is demonstrated by the synthesis of several novel glycosidase inhibitors.
Keywords: 1-N-Iminosugars; alpha-Amine radical; alpha-Trimethylsilyl methylamine radical cation; Glycosidase inhibitors; Photoinduced electron transfer (PET)

Efficient access to enantiopure 1,3-disubstituted isoindolines from selective catalytic fragmentation of an original desymmetrized rigid overbred template - Pandey, Ganesh; Varkhedkar, Rajesh; Tiwari, Divya (Organic & Biomolecular Chemistry, 2015)
An efficient and scalable synthesis of various enantiopure 1,3-disubstituted isoindolines is reported. The base catalyzed nucleophilic fragmentation of a rigid overbred template is established with various substrates to afford the corresponding 1,3-disubstituted isoindoline ester, amide, thioate, 1,3-amino alcohol and isoindolylcarboxylic acid. The crucial rigid overbred template is synthesized in an optically pure form in multigram scale by asymmetric desymmetrization of the corresponding meso compound.

Efficient strategy for the construction of both enantiomers of the octahydropyrroloquinolinone ring system: total synthesis of (+)-aspidospermidine - Pandey, Ganesh; Burugu, Shiva Kumar; Singh, Pushpendra (Organic Letters, 2016)
An efficient and highly stereoselective intramolecular [3 + 2] cycloaddition of nonstabilized azomethine ylide generated from a designed bicyclic aminal precursor is reported for the synthesis of both (-)- and (+)-octahy-dropyrroloquinolinone. One of the enantiomers is further advanced to accomplish the total synthesis of (+)-aspidospermidine.

p-Selective (sp(2))-C-H functionalization for an acylation/alkylation reaction using organic photoredox catalysis - Pandey, Ganesh; Tiwari, Sandip Kumar; Singh, Bhawana; Vanka, Kumar; Jain, Shailja (Chemical Communications, 2017)
p-Selective (sp(2))-C-H functionalization of electron rich arenes has been achieved for acylation and alkylation reactions, respectively, with acyl/alkylselenides by organic photoredox catalysis involving an interesting mechanistic pathway.

Total synthesis of (+)-trans- dihydronarciclasine from (+)-7-azabicyclo[2.2.1]heptanone - Pandey, Ganesh; Fernandes, Rushil; Dey, Debasis; Majumder, Binoy (Tetrahedron, 2018)
A concise asymmetric total synthesis of Amaryllidaceae alkaloid (+)-trans-dihydronarciclasine is accomplished starting from optically pure 7-azabicyclo[2.2.1]heptanone scaffold in 13 linear steps. Key features of the strategy include substrate-directed stereoselective installation of the trans B-C ring junction and regioselective Wacker-type internal olefin oxidation to provide a rapid access to all hydroxyl functionalities over the key cyclohexane ring in a stereocontrolled manner. (C) 2018 Elsevier Ltd. All rights reserved.

Synthesis of 2-azabicyclo[m.n.0]-alkanes and their application towards the synthesis of strychnos and stemona classes of alkaloids - Majumder, Binoy; Pandey, Ganesh (European Journal of Organic Chemistry, 2020)
2-Azabicyclo[m.n.0]alkane ring systems, the conceptual precursors towards the synthesis of Strychnos and Stemona classes of alkaloids, were synthesized from tert-butyl 2-(phenylsulfonyl)-7-aza-bicyclo[2.2.1]hept-2-ene-7-carboxylate by alkyl Grignard reaction and intramolecular cyclisation of the in situ generated ring opening product 2. The synthesized cis-hexahydroindole 3 and cis-octahydro-benzo[b]azepine 5 scaffolds were utilized to construct the advanced intermediates 25 and 35, respectively, towards the synthesis of the corresponding Strychnos and Stemona classes of alkaloids.
Keywords: alkaloids; amines; Grignard reaction; Michael addition; Natural products